Copper Electroless Metallization of Cellulose Paper via Polydopamine Coating and Silver Catalyst - Krzysztof Moraczewski (MDPI AG, 2021)
The paper presents the results of copper electroless metallization of cellulose paper with the use of a polydopamine coating and silver catalyst. The polydopamine coating was deposited via a simple dip method using a dopamine hydrochloride solution in 10 mM TRIS-HCl buffer with a pH of 8.5. The research showed that as a result of this process, cellulose fibers were covered with a homogeneous layer of polydopamine. The unique properties of the polydopamine coating allowed the reduction of silver ions from silver nitrate solution and the deposition of silver atoms on the paper surface. Deposited silver served as a catalyst in the autocatalytic electroless copper-plating process. The copper layer covered the entire surface of the paper sheet after 5 min of metallization, favorably affecting the electrical properties of this material by lowering the surface resistivity. The deposited copper layer was further characterized by good adhesive strength and high susceptibility to deformation.